Introduction to petroleum engineering - Fanchi, John R.; Christiansen, Richard L. (Wiley, 2016)
Presents key concepts and terminology for a multidisciplinary range of topics in petroleum engineering -Places oil and gas production in the global energy context -Introduces all of the key concepts that are needed to understand oil and gas production from exploration through abandonment -Reviews fundamental terminology and concepts from geology, geophysics, petrophysics, drilling, production and reservoir engineering -Includes many worked practical examples within each chapter and exercises at the end of each chapter highlight and reinforce material in the chapter -Includes a solutions manual for academic adopters.